Bronisław Piłsudski’s heritage and Lithuania - Majewicz, Alfred F. F. (Acta Orientalia Vilnensia, 2009)
Adam Mickiewicz University The paper aims at introducing the results of research on the cultures and languages of the aboriginal peoples of the island of Sakhalin, the Lower Amur Region (Priamurye), and northern Japan (Ainu, Nivhgu, Uilta, Ulcha, and Nanai) conducted at the turn of the 19th and 20th century by Polish political exile Bronisław (Ginet) Piłsudski (1866–1918) and at presenting his ties with Lithuania: he used to introduce himself as Samogitian and Lithuanian (besides Polish―here the so-called nested ethnic identity is involved) and especially towards the end of his life emphasised this identity by inserting the name of his Lithuanian ancestors before his Polish family name. His seemingly long-forgotten legacy is now brought back to the attention of specialists with the appearance of the consecutive volumes of his Collected Works. The argumentation and conclusion of this Vilnius University anniversary article is that Piłsudski belongs to the same degree to the history of Oriental studies in both Lithuania and Poland and that both countries involved can only be proud of such a figure in the annals of their intellectual heritage.